Persuading Attributes of Online Shopping Cart Abandonment - Krithika., Dr; Rajini.G, Dr (International Journal of Engineering and Technology, 2018)
The objective of this study is to focus on the variables which influencing the consumerâ€™s tendency towards online shopping cart abandonment which will happens in the final stages of the online buying process. Data for this study were collected by using an online survey. This study was conducted in Chennai. The sample consists of 185 consumers who purchased online as well as have the experience of abandoning their cart at least once during the past one-year period. The finding of this study emphasizesthatÂ theperceived waiting time is the prominent factor of online shopping cart abandonment. The otherfactors explored are perceived risk and perceived online behavioral tracking. It was also found that all these three factors such as Perceived waiting time, Perceived risk and Perceived online behavioral tracking had direct effect on online shopping cart abandonment. This study investigates the unmappedÂ part of consumer behavior.Â